Die Arbeitsbeziehungen in liberalisierten Wirtschaftsbereichen in Österreich im Vergleich - Georg Adam (Wirtschaft und Gesellschaft (WuG), 2017)
Liberalisation of public services has yielded far-reaching consequences for the organisation of industrial relations also in Austria. This contribution sets out to analyse the developments of the labour relations in five selected economic sectors having been subject to liberalisation processes – that is the post and telecommunications services, the railways sector, the gas industry and waste management services. It emerges that these five sectors widely vary in major industrial relations aspects – such as the presence of organisations of collective interest representation on the two sides of industry and the degree of homogeneity of the employment regulation within a sector – not only from the Austrian "standard pattern" for the private sector but also among each other. When it comes to identifying the possible rationale for the different paths of development, economic as well as institutional and agent-related determinants have to be distinguished. Overall, it shows that developments of the organisation of industrial relations between sectors after liberalisation do not converge; rather they proceed essentially in a path-dependent manner.
Keywords: 330; Österreich; Arbeitsbedingungen; Liberalisierung